Effect of oral doses of lead on immune response in calves - DEY, S; SWARUI, D; DWIVEDI, S K (The Indian Journal of Animal Sciences, 2013)
Influence of lead on humoral and cellular immune response was studied in healthy crossbred calves (12), divided into 2 groups, Calves of group A served as healthy control, and those of group 13 received lead acetate @ 5.0 mg/kg body weight (equivalent 10 2.73 mg of lead) till the appearance of clinical signs of toxicity. Significant decrease in humoral immune response to chicken red blood cells Was recorued in calves exposed to lead from day 28 onwards. In these calves, phagocytic index of poly morphonuclear cells and delayed hypersensitivity reaction to dinitrochloro benzene declincd significantly from days 42 and 28 postexposure respectively. Erythema, in duration and swelling or the sensitized area were not intense in calves exposed to lead as compared to healthy calves. Skin biopsy sample taken of the challenge dose of DNCB, revealed modorate ocellular infiltration in calves exposed to lead.